Heterologous production and characterization of a thermostable GH10 family endo-xylanase from Pycnoporus sanguineus BAFC 2126 - Niderhaus, Cecilia (2018)
Xylanases are key enzymes for agricultural biomass saccharification for the production of cellulosic ethanol. Success in enzymatic lignocellulose bioconversion is restricted by enzyme production costs, activity and stability under harsh reaction conditions, and their performance when interacting into cellulolytic cocktails. In this work, we present the heterologous expression and enzymatic characterization of a novel endo-β-1,4 xylanase of glycoside hydrolase family 10 (GH10ps) from the white-rot basidiomycete Pycnoporus sanguineus BAFC 2126. Recombinant expression of GH10ps in Pichia pastoris showed that it is a robust enzyme active at a wide range of pHs and temperatures, and with a half-life of 3 h at 70 °C and a stability higher than 48 h at 60 °C. Recombinant GH10ps was also capable of releasing xylooligosaccharides and xylose from pretreated agricultural waste biomass and also complemented commercial cellulases in lignocellulose bioconversion to fermentable sugars.